PERLINDUNGAN HUKUM PEMBELI HAK ATAS TANAH BERDASARKAN ALAS HAK YANG BERASAL DARI SURAT KETERANGAN CAMAT (Analisis Kasus PTUN Nomor: 72/G.TUN/2005/PTUN-MDN) - HAFNI CHOLIDA NASUTION (PREMISE LAW JURNAL, 2013)
Land certificate was underhanded written evidence which was not as powerful as the authentic deed, but since the land certificate could be categorized as the legal basis or judicial data to the land and could be used as the accessory for requesting land rights as stipulated in the legal provisions, the land certificate could become an important document in the process of issuing land rights certificate. The unlawful act in land ownership as it is used as the legal basis in the process of registering the land for the first time before the certificate is held by the last owner will cause all evidence of ownership, since the first time the unlawful act was conducted, to be legally abrogated, including the registration of the transfer of the land rights even though it is legally done. If the abrogation and the expropriation of ownership certificate cause the loss of the purchaser who has good intention, this purchaser can file a complaint to nearby District Court to claim a compensation for the execution by the verdict of the State Administrative Court. Keywords: Legal Protection, Legal Basis, Certificate of Subdistrict Head